0397 Neighborhood Physical and Social Environments and Sleep Among Children and Adolescents: A Systematic Review. (27th May 2020) - Mayne, S L; Mitchell, J A; Virudachalam, S; Williamson, A A
Abstract: Introduction: Understanding salient environmental determinants of pediatric sleep is essential for informing interventions and public health initiatives. Emerging evidence suggests the neighborhood environment can impact pediatric sleep. We are conducting a systematic review of studies examining associations of neighborhood physical and social environments with sleep among children and adolescents. Methods: We searched 6 databases (MEDLINE, PubMed, EMBASE, SCOPUS, Web of Science, PsychInfo) using search terms related to sleep, neighborhood environment, and pediatric populations to identify English-language articles with an abstract. We identified and screened 2, 581 abstracts. Inclusion criteria included 1) assessing associations of ≥1 neighborhood-level factor with ≥1 sleep outcome and 2) including participants ≤18 years. We excluded review articles, protocols, qualitative and non-human studies. In total, 134 full-text articles were independently reviewed by 2 reviewers each to confirm eligibility. One reviewer abstracted preliminary data from included studies. Next steps include independent data abstraction by two reviewers using a standardized form, synthesis of results, and assessment of study quality according to the study design, sleep assessment method, sampling strategy, and control for confounding. Results: Sixty-one articles met inclusion criteria. Fourteen articles included children aged 0-5 years, 38 included children aged 6-12 years, and 36 included adolescents aged 13-18 years (25 included multiple age groups). Twenty-two studies (36%) used objective sleep assessment methods (e.g. actigraphy). Seven studies (11%) examined sleep apnea/snoring. The most common neighborhood-level factors were safety/crime/community violence (n=28) and socioeconomic status (n=25), with fewer studies examining other exposures like noise (n=7) and social cohesion (n=4). Results on key associations and study quality are forthcoming. Conclusion: A growing body of epidemiological data has emerged in recent years to provide insight into how the neighborhood environment can impact pediatric sleep. Preliminary results suggest few studies have examined associations of the built environment with sleep, with most studies focusing on school-aged children and adolescents. Support: This work was supported by: the Children's Hospital of Philadelphia's Possibilities Project (SLM); Sleep Research Society Foundation and K23HD094905 (AAW); NIH/NHLBI K01HL123612 (JAM)